ENGLISH PRODUCED BY INDONESIAN YOUNG EFL LEARNERS - Ningrum, Yusnita Sylvia (Language Circle: Journal of Language and Literature, 2009)
This study is aimed at describing what types of English Indonesian children can produce after they learn it from school and what linguistic features are used in their English (language). The corpus of the data is a stretch of approximately sixty-minute dialogue between 5 primary school children and their teacher. Functional approach proposed by Halliday is applied in conducting this study, therefore the term Ã¢â‚¬Å“EnglishÃ¢â‚¬Â in the title of this paper later on will be exclusively understood as Ã¢â‚¬Ëœspeech functionÃ¢â‚¬â„¢. Meanwhile, the phrase Ã¢â‚¬Å“young EFL (English as a Foreign Language) learnersÃ¢â‚¬Â in the following paper is used in several similar meanings, like children, young learners, primary school learners. Using Speech Function Network developed by Eggins and Slade (1997), then, it is found out that Indonesian young EFL-learners are able to produce speech functions (English) such those of produced by adult in quite complex linguistic features. Key words: speech function, realization, English as a foreign language, primary school learners